A Case of Early Calciphylaxis Diagnosed by Bone Scan - Jia Di; Yuqiu Liu; Dongyan Wang; Min Yang (Case Reports in Medicine)
Calcium uremic aortic disease (calciphylaxis) has long been considered as a rare, life-threatening small vessel disease. The diagnosis of calciphylaxis depends mainly on clinical symptoms and high risk factors, and skin biopsy can be used to confirm the diagnosis. However, noninvasive testing methods are still the focus of exploration currently. There is increasing evidence that bone scintigraphy is helpful in the diagnosis of calciphylaxis, especially for assessing the involvement of muscles and internal organs. Here, we describe a pathology-proven case of calciphylaxis case and the corresponding imaging findings on Tc-99 m MDP bone scan imaging.